Alcohol Use Disorder Increases the Risk of Irritable Bowel Disease: A Nationwide Retrospective Cohort Study. Issue 51 (December 2015) - Hsu, Tai-Yi; He, Guan-Yi; Wang, Yu-Chiao; Chen, Chih-Yu; Wang, Shih-Hao; Chen, Wei-Kung; Kao, Chia-Hung
Abstract : Abstract: Alcohol use disorder (AUD) is considered a possible risk factor for irritable bowel syndrome (IBS); however, previous studies investigating the association between AUD and IBS have yielded inconsistent results. The study investigated whether AUD increases the risk of IBS by using a population-based database in Taiwan. This retrospective matched-cohort study included the health insurance claims data of 56, 355 AUD inpatients and 225, 420 randomly selected controls by frequency-matched for sex, age, and index year. Cox proportional hazards regression analysis was performed to measure the risk of IBS among AUD patients compared with non-AUD patients. During the follow-up period, the incidence rate ratio (IRR) of IBS had 12.3-fold (95% CI: 11.9–12.7) in the AUD patients than non-AUD patients and the adjusted hazard ratio (aHR) for IBS in the AUD patients was 5.51 (95% CI: 4.36–6.96). For several comorbidities, the risk of IBS was significantly higher in the AUD patients than in non-AUD patients, with aHRs of 2.14 (95% confidence interval [CI]: 1.19–3.84), 2.05 (95% CI: 1.06–3.96), and 2.91 (95% CI: 1.26–6.72) for sleep disorders, acute pancreatitis, and hepatitis B, respectively. When we stratified the severity of AUD according to the length of hospital stay, the aHRs exhibited a significant correlation ( P  < 0.001) with severity, yielding aHRs of 3.24 (95% CI: 2.49–4.22), 11.9 (95% CI: 8.96–15.9), and 26.1 (95% CI: 19.4–35.2) for mild, moderate, and severe AUD, respectively. The risk of IBS was higher among AUD patients, and increased with the length of hospital stay.